Los derechos humanos de los policías en México, su desempeño laboral e impacto en la criminalidad - Haro Reyes, Dante (Archivos de criminología, seguridad privada y criminalística, 2021)
The human rights of police officers are a key factor to carry out their duties and activities in favor of the population. This article details the regulatory framework for police action; as well as the labor human rights of the police that must be safeguarded. Similarly, to argue the above, the Rights in International Labor Standards are described, as well as the Rights in National Law, such the respect for Human Rights and rights in the provision of the service, as well as those of the scope of the state. In another section, the great importance of the police officers' work activity and the generation of job stress in the public security forces are detailed. And finally, what the police work implies, the violation of their rights, and the consequences that this brings in the growth and impact on crime.